2011
DOI: 10.4238/vol10-3gmr1141
|View full text |Cite
|
Sign up to set email alerts
|

Lack of an association between a single nucleotide polymorphism in the bovine myogenic determination 1 (MyoD1) gene and meat quality traits in indigenous Chinese cattle breeds

Abstract: ABSTRACT. The myogenic determination 1 (MyoD1) gene is a member of the MyoD gene family. It encodes for skeletal musclespecific transcription factors containing highly conserved basic helixloop-helix regions that perform important roles in the initiation, maintenance, and regulation of phenotypic traits. We investigated a new single nucleotide polymorphism (SNP) in the MyoD1 gene to evaluate whether this polymorphism affects meat quality traits in five Chinese indigenous cattle breeds, namely Qinchuan (QC), Xi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…This result was similar to that of a previous study of association analysis of the TaqI-RFLP locus in intron 2; individuals with genotype AA had higher values of LW, CW, and LMA compared to individuals with the AB genotype (P < 0.05) (Tian et al, 2007). In contrast, Ujan et al (2011) found that the g.624C>G polymorphism locus in exon 1 had no influence on any meat quality traits in 5 indigenous Chinese cattle breeds. Several studies have demonstrated associations between MyoD1 and growth traits.…”
Section: Discussionsupporting
confidence: 58%
“…This result was similar to that of a previous study of association analysis of the TaqI-RFLP locus in intron 2; individuals with genotype AA had higher values of LW, CW, and LMA compared to individuals with the AB genotype (P < 0.05) (Tian et al, 2007). In contrast, Ujan et al (2011) found that the g.624C>G polymorphism locus in exon 1 had no influence on any meat quality traits in 5 indigenous Chinese cattle breeds. Several studies have demonstrated associations between MyoD1 and growth traits.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, the potential genetic improvement of rabbit meat characteristics is decided by the occurrence of specific genes in rabbits. Accordingly, Wang et al (2017) proposed myogenic factor 5 (Myf5) single nucleotide polymorphism (SNPs) could be considered as a potential genetic marker for good meat quality selection in breeding programmes of Ira and Tianfu Black breed since it plays significant roles in muscle fiber formation and transcription of muscle-specific genes (Ujan et al, 2011). Apart from Myf5, calpastatin and myopalladin (MYPN) could also be considered as candidate genes for the genetic improvement of rabbit meat traits (Li et al, 2018;Wang et al, 2017).…”
Section: Genetic Factormentioning
confidence: 99%
“…Recent investigations into economic traits of NY cattle have predominantly focused on the exploration of candidate genes. For instance, research has delved into the impact of genes like SIRT1 [ 6 ] and VEGF [ 7 ] on body weight gain, FBXO32 [ 8 ] and PAX3 [ 9 ] on body length, and MYOD1 [ 10 ] on meat quality. However, there is currently no identification of genes associated with adaptive traits in NY cattle on WGS data.…”
Section: Introductionmentioning
confidence: 99%